The Evaluation of Islamic Education Teachers’ Performance - Siti Asiah Tjabolo; Lian Gafar Otaya (Jurnal Pendidikan Islam, 2019)
Teachers’ performance is one of crucial topics in education and become a global problem in improving the quality of education in many countries, including the performance of Islamic Education teachers. Therefore, this research aims to evaluate Islamic Education teachers’ performance at SMA (Sekolah Menengah Atas/Senior High School) in Gorontalo Province. The method used in this research consisted of an evaluation research with countenance stake model. The samples were 66 Islamic Education teachers taken by purposive sampling technique.  Data were obtained through observation, interview, and document study. The finding of this research shows that the Islamic Education teachers’ performance in learning planning is good. Teachers are able to design a good learning process, although the ability in selecting methods and strategies, selecting media and learning source and composing the assessment component in evaluating the learning should be improved. Because those three components are still in enough category. The performance of teachers in the implementation of learning is in good category, despite there are still some measured components that should be improved such as by doing elaboration activity, doing assessment process and furthermore program. Therefore, explicitly shows that Islamic Education teachers in Gorontalo Province performance should be evaluated. It aims to the professional development and the carrier improvement as a teacher.